Nutrient Composition of selected Snacks in South-West Nigeria - Uthman-Akinhanmi, Yewande O.; Yangomodou, O. D.; Lawal, A. O. (NIU Journal of Humanities, 2020)
The consumption of ready to eat snacks as meals is rampant in Nigeria and this has made fast foods outlets to multiply at a fast rate across all states. This study was conducted to determine the proximate and nutrient composition of snacks obtained from the south-west states in Nigeria. Ten FFF (five non-meat-based and five meat-based) were selected from ten fast food outlets from South-west Nigeria using systematic random sampling. The FF were analyzed for proximate and mineral compositions using standard laboratory procedures. The gross energy, protein, carbohydrate and total fat of FFF ranged from 205.06 to 402.92 kcal/100g, 3.49 to 12.52%, 8.10 to 71.68% and 4.39 to 23.24% respectively. Sodium content ranged from 0.64 mg to 588.57 mg/100g while potassium content was from 24.91 mg/100g to 216.13 mg/100g. Calcium:phosphorus ratio was 0.02 to 2.8 and sodium:potassium 0.03 to 3.03. Non-meat based samples had higher calcium content when compared to the meat based group P<0.05. Fat content of the samples is inversely correlated with ash and dietary fiber content P<0.01; and total carbohydrate at P<0.05. There was significant difference P<0.05 in ash within groups of fast foods, with popcorn having the highest value. Fat content of the samples is inversely correlated with ash and dietary fiber content P<0.01; and total carbohydrate at P<0.05 within the doughnut samples. This study has shown that these snacks are poor sources of dietary fiber, zinc and potassium; and have abnormally high sodium and potassium ratio which might induce the incidence of high blood pressure in regular consumers of these snacks. Keywords: Proximate Analysis, Mineral Content, Fast Foods, Monosodium Glutamate.